Osteogenic differentiation of umbilical cord and adipose derived stem cells onto highly porous 45S5 Bioglass®‐based scaffolds. Issue 3 (14th June 2014) - Detsch, Rainer; Alles, Sonja; Hum, Jasmin; Westenberger, Peter; Sieker, Frank; Heusinger, Dominik; Kasper, Cornelia; Boccaccini, Aldo R.
Abstract In the context of bone tissue engineering (BTE), combinations of bioactive scaffolds with living cells are investigated to optimally yield functional bone tissue for implantation purposes. Bioactive glasses are a class of highly bioactive, inorganic materials with broad application potential in BTE strategies. The aim of this study was to evaluate bioactive glass (45S5 Bioglass®) samples of composition: 45 SiO2, 24.5 CaO, 24.5 Na2O, and 6 P2O5 (in wt%) as scaffold materials for mesenchymal stem cells (MSC). Pore architecture of the scaffolds as well as cell behavior in the three‐dimensional environment was evaluated by several methods. Investigations concerned the osteogenic cell attachment, growth and differentiation of adipose tissue derived MSC (adMSC) compared with MSC from human full term umbilical cord tissues (ucMSC) on porous Bioglass®‐based scaffolds over a cultivation period of 5 weeks. Differences in lineage‐specific osteogenic differentiation of adMSC and ucMSC on Bioglass® samples were demonstrated. The investigation led to positive results in terms of cell attachment, proliferation, and differentiation of MSC onto Bioglass®‐based scaffolds confirming the relevance of these matrices for BTE applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1029–1037, 2015.